MODUL AJAR IPAS BERBASIS PENDEKATAN STEM UNTUK MENINGKATKAN KEMAMPUAN BERTANYA SISWA FASE A SEKOLAH DASAR - Wati Fauziati; Siti Patonah; Sukamto (Jurnal Muara Pendidikan, 2024)
IPAS teaching modules based on the STEM approach are still not widely found in the independent curriculum, especially in the lower elementary school grades. The IPAS teaching module based on the STEM approach can help students learn with a new approach to improve their ability to ask questions for students. The study aims to analyze the level of validity of the STEM approach-based IPAS teaching module on Healthy Living Behavior material to improve the ability to ask phase A students. This type of research is development research (R&D) with the ADDIE model, which has stages in the form of analysis, design, development, implementation, and evaluation. The research was carried out at SDN 1 Tanjungmojo with the research object of 41 students in class II, with details of 22 boys and 19 girls. Data collection methods were interviews, questionnaires, tests, and observations. The validation analysis of the teaching module was carried out using the Aiken Index. The results showed that the STEM approach-based IPAS teaching module on healthy living behavior material at the validation stage obtained a result of 0.96 on the teaching module component, 0.98 on material validation, and 0.97 on language validation. This shows that the validity of the STEM-based IPAS teaching module on healthy living behavior material meets high criteria, so it is suitable for use in learning IPAS in phase A elementary schools.